Correlation and evaluation of computed tomographic scan findings with findings of functional endoscopic sinus surgery in cases of chronic rhinosinusitis - Killu, Sridevi; Dakkata, Suman Reddy; Sreerama, Surya Prakasa Rao (International Journal of Research in Medical Sciences, 2022)
Background: To correlate between computed tomography (CT) findings and the endoscopic findings in functional endoscopic sinus surgery (FESS) of chronic rhinosinusitis (CRS). Methods: Clinically diagnosed 50 cases of chronic rhinosinusitis, who underwent CT-PNS scan and FESS during the period from July 2019 to September 2021 at department of ENT, government ENT hospital, Peddawaltair, Visakhapatnam, were selected by random sampling method. The findings of CT scan and FESS evaluated and the correlation was assessed using Chi-square test and kappa statistics. Results: Hypertrophy of the inferior turbinate was the most obvious finding in CT (71%) and during FESS (69%). The most common co-morbidity found among the patients with chronic sinusitis was allergy in 35% (18) patients. Most of the important findings like mucosal thickness, osteomeatal complex (OMC) patency, hypertrophy of turbinates, septal deviation, polyp, Concha bullosa were detected both in CT and FESS and show good correlation No significant correlation was found between clinical symptoms and gender or duration of disease. Conclusions: There are good to excellent correlations between the two procedures. In spite of a good agreement between CT and FESS findings in most patients, in some unusual cases, CT may miss some findings. The value of FESS is more because of its therapeutic value. From this study it is evident that CT can complement FESS to a great extent.